The bit-serial piple-Une division method for any forms of one’s comCOMPLEMENT GOLDEN 1-RATIO CODES - Азаров, О. Д.; Черняк, О. І. (Problems of Informatization and Control, 2011)
The bit-serial pipe-line division method in golden 1-ratio numerical system, which allows to decrease interval between serial codes of operands and delay of quotient codes pipe, are suggested. The structural organization of device, which release this method and have less hardware, is developed